Teachers' perceptions of education support structures in the implementation of inclusive education in South Africa - Nel, N.M.; Tlale, L.D.N.; Engelbrecht, P.; Nel, M. (AOSIS, 2016)
Inclusive education forms the ethos of the education system in South Africa and resonates with the Constitution of the country, which recognises diversity and resists exclusivity. Inclusive education is also reflected in education policies such as the Education White Paper 6: Special Education - Building an Inclusive Education and Training System and the Screening, Identification, Assessment and Support (SIAS) document. Pivotal to inclusive education is the provision of support for all learners and teachers. The focus of this paper is on the functionality of all the formal support structures that are in place for teachers and learners from the teachers' viewpoints. These support structures include District-Based Support Teams (DBSTs), Institutional-Level Support Teams (ILSTs), Full-Service Schools (FSS), Special Schools as Resource Centres (SSRC), Learning Support Educators (LSEs) and the community. An interpretive research paradigm was chosen, using convenience sampling and data was collected by means of focus group interviews. Constant comparative data analysis was employed. Peer review and member checks were used to ensure trustworthiness. The themes that emerged were: support provided by teachers; the role of official support structures and special schools and community collaboration. It was evident, from the teachers' point of view, that the formal support structures are not as effective, as proposed by policy and educational authorities, and that the policy needs serious re-consideration.
Keywords: District-Based Support Teams; Institutional-Level Support Teams; Full-Service Schools; Special Schools as Resource Centres; Learning Support Educators; Inclusive education